2000
DOI: 10.1074/jbc.275.15.10905
|View full text |Cite
|
Sign up to set email alerts
|

Plakoglobin Regulates the Expression of the Anti-apoptotic Protein BCL-2

Abstract: Plakoglobin is a cytoplasmic protein and a homologue of ␤-catenin and Armadillo of Drosophila with similar adhesive and signaling functions. These proteins interact with cadherins to mediate cell-cell adhesion and associate with transcription factors to induce changes in the expression of genes involved in cell fate determination and proliferation. Unlike the relatively well characterized role of ␤-catenin in cell proliferation via activation of c-MYC and cyclin D1 gene expression, the signaling function of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 39 publications
4
67
0
1
Order By: Relevance
“…This would be consistent with data implicating plakoglobin in the development of squamous cell carcinoma through induction of Bcl-2 (Hakimelahi et al, 2000). Nuclear accumulation of plakoglobin and an increase in Bcl-2 expression has also been observed in advanced prostate cancer (Shiina et al, 2005).…”
Section: Desmosomes and Apoptosis In Rnd3-depleted Cellssupporting
confidence: 79%
“…This would be consistent with data implicating plakoglobin in the development of squamous cell carcinoma through induction of Bcl-2 (Hakimelahi et al, 2000). Nuclear accumulation of plakoglobin and an increase in Bcl-2 expression has also been observed in advanced prostate cancer (Shiina et al, 2005).…”
Section: Desmosomes and Apoptosis In Rnd3-depleted Cellssupporting
confidence: 79%
“…Unlike b-catenin, plakoglobin is a strong activator of c-myc, which is thought to be essential for plakoglobin's transforming ability. Another suggestion is that plakoglobin causes unregulated growth and foci formation (in human squamous carcinoma cells), as a result of induction of the pro-survival gene Bcl-2 and inhibition of apoptosis (Hakimelahi et al, 2000). In support of the latter idea, mutations within or near to a glycogen synthase kinase-3b consensus phosphorylation site have been discovered in advanced hormone refractory prostate cancer, and these coincide with strong nuclear accumulation of plakoglobin and a concomitant increase in Bcl-2 (Shiina et al, 2005).…”
Section: Plakoglobin and Cancermentioning
confidence: 73%
“…Previous findings in our laboratory indicate that the anti-apoptotic gene bcl-2 is regulated by Wnt signaling (60); in fact, lithium, a compound that mimics Wnt signaling activation (94), and Wnt-3a ligand cause a timedependent increase in bcl-2 mRNA levels in primary rat hippocampal neurons (60). Also, the ␤-catenin analogue plakoglobin induces bcl-2 expression (95). Previous findings have demonstrated that A␤ decreases neuronal bcl-2 protein levels in vitro (96) and that bcl-2 immunoreactivity is reduced in tangle-bearing neurons of AD patients (97).…”
Section: Effect Of the Wnt Signaling Pathway On The Cytoplasmic Calcimentioning
confidence: 99%